Synergistic effects of SAP and PGPR on physiological characteristics of leaves and soil enzyme activities in the rhizosphere of poplar seedlings under drought stress - Jing, Dawei; Liu, Fangchun; Li, Shanwen; Dong, Yufeng (Frontiers in Plant Science, 2024)
Super absorbent polymers (SAP) provide moisture conditions that allow plant growth-promoting rhizobacteria (PGPR) to enter the soil for acclimatization and strain propagation. However, the effects of SAP co-applied with PGPR on the physiological characteristics of leaves and rhizosphere soil enzyme activities of poplar seedlings are not well understood. Here, a pot experiment using one-year-old poplar seedlings with five treatments, normal watering, drought stress (DR), drought stress + SAP (DR+SAP), drought stress + Priestia megaterium (DR+PGPR) and drought stress + SAP + P. megaterium (DR+S+P), was performed to analyze the contents of non-enzymatic antioxidants, osmotic regulators and hormones in leaves, as well as rhizosphere soil enzyme activities. Compared with normal watering, the DR treatment significantly decreased the contents of dehydroascorbate (DHA; 19.08%), reduced glutathione (GSH; 14.18%), oxidized glutathione, soluble protein (26.84%), indoleacetic acid (IAA; 9.47%), gibberellin (GA) and zeatin (ZT), the IAA/abscisic acid (ABA), GA/ABA, ZT/ABA and (IAA+GA+ZT)/ABA (34.67%) ratios in leaves, and the urease and sucrase activities in the rhizosphere soil. Additionally, it significantly increased the soluble sugar, proline and ABA contents in leaves. However, in comparison with the DR treatment, the DR+S+P treatment significantly increased the DHA (29.63%), GSH (15.13%), oxidized glutathione, soluble protein (29.15%), IAA (12.55%) and GA contents, the IAA/ABA, GA/ABA, ZT/ABA and (IAA+GA+ZT)/ABA (46.85%) ratios in leaves, and the urease, sucrose and catalase activities in rhizosphere soil to different degrees. The soluble sugar, proline and ABA contents markedly reduced in comparison to the DR treatment. The effects of the DR+SAP and DR+PGPR treatments were generally weaker than those of the DR+S+P treatment. Thus, under drought-stress conditions, the simultaneous addition of SAP and P. megaterium enhanced the drought adaptive capacities of poplar seedlings by regulating the non-enzymatic antioxidants, osmotic regulators, and endogenous hormone content and balance in poplar seedling leaves, as well as by improving the rhizosphere soil enzyme activities.